Purification and characterization of two novel β-glucosidases from Penicillium oxalicum and their application in bioactive ginsenoside production. (August 2014) - Gao, Juan; Wang, Jiao; Cui, Jing; Wang, Nan; Bai, Yeming; Yuan, Ye; Zhou, Yifa
Abstract The fungus Penicillium oxalicum is able to selectively metabolize the 20(S)-protopanaxadiol ginsenosides Rb1, Rb2 and Rc to the bioactive ginsenoside compound K using extracellular glycosidases. In this study, two novel extracellular ginsenoside-hydrolyzing enzymes GH3-1 and GH3-2 were purified and characterized from P. oxalicum culture. Using ginsenosides as substrates, GH3-1 and GH3-2 synergistically catalyzed the hydrolysis of Rb1, Rb2 and Rc to yield the final product Compound K (C-K). The hydrolysis pathways were determined to be: Rb1→Rd→F2→C-K, Rb2→CO→CY→C-K and Rc→Mb→Mc→C-K for GH3-1 and GH3-2, respectively. The two enzymes differ, especially in composition, molecular weight, stability and substrate specificity, from GH1, a glycosidase previously purified from the same fungus. These enzymes could be of interest in glycoside degradation, especially in the production of minor ginsenosides.